Coexistence of thymoma and necrotizing pneumonia: a case report with a fatal outcome - Nieves-Condoy, Jefferson Fabian; Acuña-Pinzón, Camilo Levi; Narváez-Fernández, Salvador; Chavarría-Chavira, José Luis; Crocco-Quirós, Bruno; Rivera-Márquez, Daniel Augustin (International Surgery Journal, 2021)
Thymoma is an entity with an estimated incidence of 1.2-3.2 per million people, with a prognosis and treatment determined by its clinical stage and histological classification, the most widely used classification systems being the Masaoka-Koga for clinical stage and that of the world health organization (WHO) for histology. Necrotizing pneumonia is another rare entity that was initially described in adults in the 1940s; however, it is currently being studied more extensively in the pediatric setting, and currently its treatment, especially in adults, is unclear and surgical treatment usually reserved in the presence of complications and poor response to medical management. The coexistence of two rare entities is a problem for which therapeutic options are limited; the general condition of the patient is a determining factor in the outcome in a critically ill patient. In the present case, the association of two infrequent entities is reported, which presented a pneumothorax as a complication that required placement of an endo-pleural tube for drainage, pre-surgical biopsy a B1 thymoma was reported. The post-surgery pathology report was an encapsulated thymoma, WHO type A, the broad-spectrum antibiotic management did not prevent the dissemination of the septic focus in the context of a patient with malnutrition and immunosuppression.